The Shipwreck and the Wreath. Dissolution of Identities in Ruta Sepetys’ Salt to the Sea - Lukaszyk, Ewa (Literatūra, 2025)
The article presents a reading of Ruta Sepetys’ novel Salt to the Sea in the context of the philosophical proposal of Hans Blumenberg, who tried to capture the dynamics of European cultural and intellectual history through the metaphor of shipwreck. This pessimistic theory of modernity as a cycle of catastrophes is counterbalanced by the new vision of transcultural becoming and the theory of dissolution of cultures proposed by Wolfgang Welsch. The analysis of Sepetys’ literary vision of the end of the Second World War accentuates the element of deconstruction of monolithic identities and their manipulative potential. Instead, individual decisions and responsibility come to the fore. The metaphor of the Saint John’s Night traditional wreath, expressing the idea of the intermingling of minor identifications and the plurality of origins, is suggested as a substitute for the ominous metaphor of shipwreck proposed by Blumenberg as a key for the understanding of a new epoch of European history.
Keywords: Ruta Sepetys; transcultural literature; identity; displacement; shipwreck